PERBEDAAN METODE CERAMAH DAN VIDIO TERHADAP PENGETAHUAN REMAJA TENTANG SEKS PRANIKAH TAHUN 2021 - Rahmi Sari Kasoema; Resty Noflidaputri; Visti Delvina; Nanda Nadila (HUMAN CARE JOURNAL, 2022)
WHO data (2017), 0.9% of adolescent girls and 3.6% of adolescent boys in developing countries had sexual intercourse. Based on KPAI data (2017), 62.7% of teenagers in Indonesia had sex outside of marriage. For this reason, it is necessary to provide health education about reproductive health among adolescents, especially about premarital sex. This study aimed to look at the Differences between Lecture and Video Methods Toward Adolescent Knowledge of Premarital Sex at SMPN 2 Koto Baru Dharmasraya in 2021.The type of this study was Quasy Experiment  with a two group pretest-posttest design which was conducted . It was conducted at SMPN 2 Koto Baru Dharmasraya from February to July 2021. The population was all teenage girls at the second grade. They were 120 people. By using purposive sampling technique, 10 people for the lecture method. and 10 people for the video method were chosen as the samples. The data were collected by questionnaire. Then, it was analyzed by univariate and bivariate analysis by using independent t-test statistical test.The results showed that the average knowledge of the students about premarital sex before was 7.20 and after being given health counseling the lecture method was 11.60. The average knowledge of the students about premarital sex before was 7.70 and after being given health counseling with the video method was 15.00. Then, there were differences in the knowledge of students before and after being given health counseling with the lecture method (p = 0.000) and before and after being given health counseling with the video method (p = 0.000). There was a difference in the knowledge of students after counseling between the lecture method and the video method about premarital sex (p = 0.001).In short, can be concluded that there were differences in the knowledge of students before and after being given health counseling with the lecture and video methods and there were differences in the lecture and video methods on students’ knowledge about premarital sex. It is hoped that the school will do the cooperation with local health workers in conducting health education. or socialization of adolescent reproductive health, especially the dangers of premarital sex in adolescents.